Feasibility study of e-assessment acceptance from teacher's perspective [electronic resources] - 579570 Imtiaz, Md Athar; Faculty of Advanced Informatics School (2014)
Thesis (Sarjana Sains (Pengurusan Teknologi Maklumat)) - Universiti Teknologi Malaysia, 2014